Nicotine Enhances Alerting, but not Executive, Attention in Smokers and Nonsmokers - Myers, Carol S. (Oxford University Press, 2013)
INTRODUCTION: Difficulty concentrating is a symptom of nicotine withdrawal that can contribute to relapse in individuals trying to quit smoking. The purpose of this study was to determine the effects of nicotine on executive and alerting attention in smokers and nonsmokers. METHODS: Thirty daily smokers who were not tobacco deprived and 30 nonsmokers participated in the study. Participants received a single dose of intranasal nicotine (0, 0.5, or 1.5 mg) at each of 3 experimental sessions on separate days. Participants completed subjective ratings and 3 attention tasks before and after nicotine administration. RESULTS: Nicotine had no effect on executive attention as assessed by a Rapid Serial Visual Presentation (RSVP) task or the Attention Network Test in smokers and nonsmokers. In contrast, nicotine enhanced alerting attention by decreasing errors on a Continuous Performance Test (CPT) in nonsmokers and improving the correct identification of target words on the RSVP task in smokers. Nonsmokers were more sensitive than smokers to the subjective, but not the cardiovascular, effects of nicotine. CONCLUSIONS: The acute administration of intranasal nicotine improved alerting attention in nonsmokers as measured by the CPT, and in smokers as measured by the RSVP. Understanding the elements of attention enhanced by nicotine might guide the development of novel medications for tobacco dependence.